A Study On The Awareness And Problems Of Customers Towards Digital Banking Services - Vasudeva D.M; Prof. P. Paramashivaiah (Educational Administration: Theory and Practice, 2023)
In India, banks are essential to the country’s economic growth. They mobilise public savings and provide a range of services. The banking industry saw new banking techniques after the economic changes in 1991. The Saraf Committee, which was established by the Reserve Bank of India in 1994 and proposed the deployment of the Electronic Fund Transfer System (EFT). Digital banking refers to financial transactions made online. Customers may conduct financial transactions more easily thanks to digital banking services. It offers financial services round-the-clock. The government wants to digitise every transaction with the establishment of financial inclusion in the year 2005. The goal of the government is to digitise every transaction. Only when clients are aware of the service and its mode of operation can they use digital banking services. Therefore, it is important to understand how much people are aware of online banking services and the issues they encounter. A total of 235 respondents from urban and rural areas were chosen for the study using a simple random sample procedure. The study is restricted to the State Bank of India in karnataka. According to the report, ATM cards are the digital banking service that clients are most familiar with, and complicated transaction processes are the main issue they encounter. There is a suggestion that SBI should increase public knowledge about all the digital banking services.